Mapping the distribution of neurotransmitters to resting-state functional connectivity in Parkinson's disease - Li, Weihua; Lao-Kaim, Nicholas P.; Li, Runtian; Martín-Bastida, Antonio; Roussakis, Andreas Antonios; Searle, Graham E.; Valle-Guzman, Natalie; Dayal, Viswas; Athauda, Dilan; Kefalopoulou, Zinovia; Mahlknecht, Philipp; Church, Alistair; et al. (Brain Communications, 2025)
Dopamine and serotonin are two major monoamine neurotransmitters associated with Parkinson's disease (PD), but their spatial distribution and relationship to underlying functional brain architecture are not fully understood. We assessed 30 patients with PD at baseline using structural MRI, resting-state functional MRI (rs-fMRI), 11C-PE2I and 11C-DASB PET, along with comprehensive clinical evaluations of motor and non-motor symptoms. Of these, 15 patients with PD who completed the same assessments after 19 months were included in the longitudinal analysis. rs-fMRI was used to assess functional connectivity, while 11C-PE2I and 11C-DASB PET were used to evaluate interregional homogeneity of dopamine and serotonin levels, referred to as PET covariance. Functional connectivity and PET covariance were estimated using a region-of-interest (ROI)-based approach with 138 ROIs from the Automated Anatomical Labelling 3 atlas, excluding cerebellar regions. These ROIs were further grouped into eight networks: visual, sensorimotor, attention, limbic, frontoparietal, default mode, subcortical and brainstem. At baseline, linear regression revealed that functional connectivity was positively associated with both 11C-PE2I PET covariance (β-values ranging from 0.575 to 0.790, P < 0.001) and 11C-DASB PET covariance (β-values ranging from 0.356 to 0.773, P < 0.001) across all networks. Longitudinally, we found positive correlations between baseline functional connectivity and both 11C-PE2I PET change covariance and 11C-DASB PET change covariance (β-values ranging from 0.166 to 0.576 and 0.312 to 0.671, respectively, P < 0.001) across all networks. These correlations remained significant after controlling for the Euclidean distance between ROIs, indicating that the association is independent of spatial proximity. For both tracers, absolute PET uptake across seed ROIs was positively associated with correspondent regression-derived functional connectivity-PET β-weights, which represent the relationship between PET uptake in target ROIs and their functional connectivity to the seed. This association between target functional connectivity and PET uptake was correlated with PD motor and non-motor severity across different brain regions in a manner that was dependent on the neurotransmitter system evaluated. Our findings suggest that in patients with PD, dopamine and serotonin levels covary among brain regions that are highly functionally connected. This implies that the spatial distribution of these neurotransmitters follows the organizational principles of the brain's functional connectomes, which are associated with features of the disease.
Keywords: dopamine; functional connectivity; Parkinson's disease; PET imaging; serotonin